Distribution System Administration Analysis In PT. Indonesian Cement Distributors West Nusa Tenggara - Evi Purnika Yuwandari; Bambang Triaji; Didin Hadi Saputra; M. Nasuhi; Mufidah Mufidah (Universitas Negeri Makassar, 2022)
The purpose of this study is to determine the distribution system administration activity model at PT. Semen Indonesia Distributor of West Nusa Tenggara and to analyze administrative processes in the cement distribution system at PT. Semen Indonesia Distributor West Nusa Tenggara. While the analytical method used is descriptive qualitative analysis with the data analysis technique of the Miles & Huberman interactive model, namely, data collection, data reduction, data presentation, and drawing conclusions. Based on the results of research, it is known that the administration system process at PT. Semen Indonesia Distributor West Nusa Tenggara starts from requesting stock of goods, receiving goods from the warehouse, releasing goods to the warehouse, sales and finance using SID Mobile based on SAP (system analysis and product in data processing) with the Material Management (MM) application module , Sales Distribution (SD), and Finance and Control (FICO)